Why Bankers Ration Credit - Freimer, Marshall; Gordon, Myron J. (Quarterly Journal of Economics, 1965)
I. Introduction, 397. — II. Variation in optimal loan with interest rate on a fixed-size investment, 399. — III. Variation in optimal loan with interest rate on an open-end investment, 405. — IV. Aversion to risk and other factors which reduce variability in interest rates, 408. — V. Factors which cause some variation in interest rates, 415.